INFLUENCE OF NUTRITION COMPOSITIONS ON MICROCLONAL PROPAGATION DIFFERENT GENOTYPES OF THE WALNUT JUGLANS REGIA L - T. K. Yegizbayeva; T. V. Yausheva; S. N. Oleichenko; R. J. Licea-Moreno (Scientific Journal of Pedagogy and Economics, 2020)
Walnut is one of the most common nuts in many countries of the world. It is used in cooking and in traditional medicine. Walnut cultivation on an industrial scale in Kazakhstan began only in 2016-2017, so Kazakhstan scientists in this field do not yet have any scientific experience. The article presents the results of studies on the influence of the nutrient medium compositions Murashige-Skoog and Driver-Kunzhuki on the microclonal propagation of different genotypes of the walnut Juglans regia L. Two varieties were selected as mother plants: the Uzbek variety Ideal and the Chinese variety Liaohe-1, adapted in the southeast Kazakhstan. In the course of work, we compared the growth rate of walnut shoots of two varieties on nutrient media Murasige-Skoog (MS) and Driver-Kunzhuki (DKW) with a concentration of 6-benzylaminopurine (BAP) of 1 and 1.5 mg / l. After a month of cultivation of shoots, positive growth dynamics was observed only on MS medium. On plants of both varieties, the growth rate was slow on DKW medium, the plants had yellow leaves, some shoots blackened and perished. To obtain high-quality material, as well as to increase the growth rate of shoots, DKW medium was supplemented with FeEDDHA (119 mg / L) and phloroglucinol (50 mg / L). As a result of phenological observations: the height of the main shoot, the number of internodes, the formation of additional shoots, and the state of the plants, it was found that the best nutrient medium for microclonal propagation of walnut Ideal and Liaohe-1 is a modified DKW medium. MS can only be used at the initial stage - an introduction to in vitro culture.